VDR hypermethylation and HIV‐induced T cell loss. Issue 4 (1st April 2013) - Chandel, Nirupama; Husain, Mohammad; Goel, Hersh; Salhan, Divya; Lan, Xiqian; Malhotra, Ashwani; McGowan, Joseph; Singhal, Pravin C.
Abstract : HIV‐induced T cell loss was mediated through ROS generation in response to HIV‐induced VDR methylation and associated activation of the RAS. Abstract : Epigenetics contributes to the development of variety of diseases by modulation of gene expression. We evaluated the effect of HIV‐induced VDR methylation on loss of TCs. HIV/TC displayed enhanced VDR‐CpG methylation and increased expression of Dnmt3b but attenuated expression of VDR. A demethylating agent, AZA, inhibited this effect of HIV. HIV/TC also displayed the activation of the RAS, which was reversed by EB (a VDA). Further, HIV/TCs displayed enhanced generation of ROS and induction of DSBs but attenuated DNA repair response. However, in the presence of AZA, EB, LOS (a RAS blocker), Cat, and tempol (free radical scavengers), HIV‐induced TC ROS generation and induction of DSBs were attenuated but associated with enhanced DNA repair. Additionally, AZA, EB, and LOS provided protection against HIV‐induced TC apoptosis. These findings suggested that HIV‐induced TC apoptosis was mediated through ROS generation in response to HIV‐induced VDR methylation and associated activation of the RAS.